Women with heart disease: can the common-sense model of illness help? - Shifren K (Health Care for Women International, 2003)
Noncompliance with cardiac rehabilitation programs is a major concern for female coronary heart disease patients. In this article I argue for the use of the common-sense model of illness in developing interventions to increase compliance with cardiac rehabilitation programs among women with heart disease. First, the common-sense model of illness is discussed. Second, a personal narrative technique that addresses the key components of the common-sense model of illness is presented. I recommend that a modified version of the personal narrative technique be used to increase women's compliance with cardiac rehabilitation programs because this technique is well suited for women's health issues.